Library management - McCafferty, Bridgit (Rowman & Littlefield, 2021)
Section I: Project Management – Chapter 1: The Role of the Project Manager – Chapter 2: Leadership Styles – Chapter 3: Group Development and Conflict – Chapter 4: Project Management Frameworks – Chapter 5: Assessment Basics – Chapter 6: Developing Professionally through Project Management – Section II: Middle Management – Chapter 7: The Role of a Middle Manager – Chapter 8: Mentoring and Managing Employees – Chapter 9: Coordinating Resources – Chapter 10: Strategic Planning and Assessment – Chapter 11: Promoting and Transforming Organizational Culture – Chapter 12: Developing Professionally through Middle Management – Section III: Upper Management – Chapter 13: The Role of a Director – Chapter 14: Managing Managers and Managing Up – Chapter 15: Crisis Leadership – Chapter 16: Budgeting – Chapter 17: Getting Support – Chapter 18: Peer Review, Accreditation, and Assessment – Chapter 19: Developing Professionally through Upper Management.
Literaturverzeichnis: Seite 153 - 156
Keywords: Library administrators; Library administration; Project management; Leadership